2019
DOI: 10.3390/cryst9070340
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Chemical Composition of Lithium Niobate Powders

Abstract: Existent methods for determining the composition of lithium niobate single crystals are mainly based on their variations due to changes in their electronic structure, which accounts for the fact that most of these methods rely on experimental techniques using light as the probe. Nevertheless, these methods used for single crystals fail in accurately predicting the chemical composition of lithium niobate powders due to strong scattering effects and randomness. In this work, an innovative method for determining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Oswaldo et al. [ 42 ] have reported the following formulas for determining niobium content in LN powder at ∼876 cm −1 : CNbL[]mol%badbreak=[256.4103×normalΓnormalL/2normalxnormalc+43.5385]±0.4,\begin{equation}{\left( {{{\rm{C}}_{{\rm{Nb}}}}} \right)_{\rm{L}}}\left[ {{\rm{mol}}\% } \right] = [256.4103 \times \left( {{\Gamma _{\rm{L}}}/2{{\rm{x}}_{\rm{c}}}} \right) + 43.5385] \pm 0.4,\end{equation} CNbG[]mol%badbreak=[588.2353×normalΓnormalG/2normalxnormalc+42.7059]±0.5.\begin{equation}{\left( {{{\rm{C}}_{{\rm{Nb}}}}} \right)_{\rm{G}}}\left[ {{\rm{mol}}\% } \right] = [588.2353 \times \left( {{\Gamma _{\rm{G}}}/2{{\rm{x}}_{\rm{c}}}} \right) + 42.7059] \pm 0.5.\end{equation}…”
Section: Composition and Bonding Characterization Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oswaldo et al. [ 42 ] have reported the following formulas for determining niobium content in LN powder at ∼876 cm −1 : CNbL[]mol%badbreak=[256.4103×normalΓnormalL/2normalxnormalc+43.5385]±0.4,\begin{equation}{\left( {{{\rm{C}}_{{\rm{Nb}}}}} \right)_{\rm{L}}}\left[ {{\rm{mol}}\% } \right] = [256.4103 \times \left( {{\Gamma _{\rm{L}}}/2{{\rm{x}}_{\rm{c}}}} \right) + 43.5385] \pm 0.4,\end{equation} CNbG[]mol%badbreak=[588.2353×normalΓnormalG/2normalxnormalc+42.7059]±0.5.\begin{equation}{\left( {{{\rm{C}}_{{\rm{Nb}}}}} \right)_{\rm{G}}}\left[ {{\rm{mol}}\% } \right] = [588.2353 \times \left( {{\Gamma _{\rm{G}}}/2{{\rm{x}}_{\rm{c}}}} \right) + 42.7059] \pm 0.5.\end{equation}…”
Section: Composition and Bonding Characterization Methodsmentioning
confidence: 99%
“…Schlarb et al suggested using only the 876 cm −1 mode. [4,5] Oswaldo et al [42] have reported the following formulas for determining niobium content in LN powder at ∼876 cm −1 :…”
Section: Backscattering or Forward-scattering Configuration Modesmentioning
confidence: 99%
“…Therefore, the development of the precise analysis method to detect the chemical composition (Li content) of LiNbO 3 is very important. Table 2 shows available testing methods for determine Li content of LiNbO 3 , for example, X-ray diffraction (XRD), Raman spectroscopy (RS), UV-vis diffuse reflectance (DR), and differential thermal analysis (DTA) [31][32][33][34][35][36]. In Raman spectroscopy, the Li content can be calculated according to the linewidth (Γ) at 876 cm −1 [37][38][39].…”
Section: Composition Characterizations Of Linbomentioning
confidence: 99%
“…In paper [4], determination of chemical composition between congruent and stoichiometric LiNbO 3 powders was worked out by four analytical techniques. Sample preparations were done by mechanosynthesis.…”
Section: Linbo 3 Preparation Techniquesmentioning
confidence: 99%